Crystallographic and NMR Study of Streptococcus pneumonia LCP Protein PsrSp Indicate the Importance of Dynamics in Four Long Loops for Ligand Specificity - Tatyana Sandalova; Benedetta Maria Sala; Martin Moche; Hans-Gustaf Ljunggren; Evren Alici; Birgitta Henriques-Normark; Tatiana Agback; Dmitry Lesovoy; Peter Agback; Adnane Achour (Crystals)
The crystal structure of the extracellular region of the second pneumococcal LCP, a polyisoprenyl-teichoic acid-peptidoglycan teichoic acid transferase PsrSp, was determined and refined to 2.15 Å resolution. Despite the low sequence homology with other LCP proteins, the PsrSp maintains the fold of the LCP domain, and the positions of the residues suggested to participate in the transferase function are conserved. The tunnel found in the PsrSp between the central β-sheet and three α-helices is wide enough to accommodate polyisoprenyl-teichoic acid. Comparison of the crystallographic temperature factors of LCP from distinct bacteria demonstrated that the four long loops located close to the teichoic acid and peptidoglycan binding sites have different relative mobilities. To compare the dynamics of the PsrSp in crystalline state and in solution, NMR spectra were recorded, and 88% of the residues were assigned in the 1H-15N TROSY HSQC spectra. Perfect accordance in the secondary structure of the crystal structure of PsrSp with NMR data demonstrated correct assignment. Moreover, the relative mobility of the essential loops estimated from the crystallographic B-factor is in good agreement with order parameter S2, predicted from chemical shift. We hypothesize that the dynamics of these loops are important for the substrate promiscuity of LCP proteins.